Reduction of enantioselectivity in the kinetic disposition and metabolism of verapamil in rats exposed to toluene - Mateus, F. H.; Lepera, José Salvador [UNESP]; Marques, M. P.; Boralli, V. B.; Lanchote, V. L. (Canadian Science Publishing, Nrc Research Press, 2008)
Toluene and verapamil are subject to extensive oxidative metabolism mediated by CYP enzymes, and their interaction can be stereoselective. In the present study we investigated the influence of toluene inhalation on the enantioselective kinetic disposition of verapamil and its metabolite, norverapamil, in rats. Male Wistar rats (n = 6 per group) received a single dose of racemic verapamil (10 mg/kg) orally at the fifth day of nose-only toluene or air (control group) inhalation for 6 h/day (25, 50, and 100 ppm). Serial blood samples were collected from the tail up to 6 h after verapamil administration. The plasma concentrations of verapamil and norverapamil enantiomers were analyzed by LC-MS/MS by using a Chiralpak AD column. Toluene inhalation did not influence the kinetic disposition of verapamil or norverapamil enantiomers (p > 0.05, Kruskal-Wallis test) in rats. The pharmacokinetics of verapamil was enantioselective in the control group, with a higher plasma proportion of the S-verapamil (AUC 250.8 versus 120.4 ng.h.mL(-1); p <= 0.05, Wilcoxon test) and S-norverapamil (AUC 72.3 versus 52.3 ng.h.mL(-1); p <= 0.05, Wilcoxon test). Nose-only exposure to toluene at 25, 50, or 100 ppm resulted in a lack of enantioselectivity for both verapamil and norverapamil. The study demonstrates the importance of the application of enantioselective methods in studies on the interaction between solvents and chiral drugs.
Keywords: verapamil; pharmacokinetics; toluene; nose-only exposure; CYP; rats